Silvio Julio de Albuquerque Lima: um precursor dos estudos acadêmicos sobre a América Hispânica no Brasil - Priscila Ribeiro Dorella (2006)
This work brings forward the intellectual trajectory of Silvio Julio deAlbuquerque Lima, an academic pioneer of the Spanish American studies in Brazil. Since the XIX century, the Brazilian intellectuality elaborated speeches, mainly negative, about the Spanish America. The authors choice had as basic premise his vision being one of the first counterpoints to this tendency, which lets us enlarge the reflection about Latin American in Brazil. The study brings the analysis of the interpretations by Silvio Julio about Latin American and discusseshow his militancy for the mutual knowledge of these countries, along with his temperamental behavior strongly, contributed to turn him into forgotten and out of place intellectual. The authors trajectory shows his insertion in the utopic Latin American tradition, which tells the approximation among these countries to be an essential factor for their cultural, political and economic development.